Through the Hourglass: New Play Development at Tarragon and Nightswimming - Iacobellis, Laurren (Université d'Ottawa / University of Ottawa, 2012)
This study proposes and tests a model for play development analysis, which offers a framework and a vocabulary for cataloguing the working parts of play development initiatives. When scholars analyze a completed play text, there are several useful categories available with which to organize observations, including space and time, character, dialogue, plot and story, genre, and spectacle. Such basic categories have been lacking in the analysis of play development and dramaturgy practice. In order to create a framework for analysis, the hourglass model for play development analysis proposes the basic categories of source, perspective, leadership, company modelling, choice of form, conditions of creation (including assumed theatrical conventions), design, given and anticipated consequences, and reception. The three case studies included in this project demonstrate the uses and limitations of the analysis model for new play development and its categories. The Whispering Pines play development process at Nightswimming and the processes experienced by the participants in the 2011 Tarragon Playwright’s Unit both fit easily into the hourglass, largely because they employ traditional roles in the play development process without challenging established hierarchies and because both resulted in play texts; Nightswimming’s Rough House, as a devised piece, challenges the model and demonstrates its flexibility in dealing with non-traditional forms of theatre-making. By providing grounds for comparison between these three markedly different models, the hourglass teases out a number of productive contrasts between text-based and devised theatre. The model which I propose and test in this study has been designed to introduce a formal, pragmatic methodology to the heretofore anecdotal field of scholarship on English-Canadian dramaturgy and new play development. Its formation is indebted to and embedded within the scholarship which has come before. The pragmatic model is proposed as a methodological framework for analysis that has yet to be employed in scholarship on dramaturgy practice and new play development in particular. In my analysis of three play development initiatives, I identify the common elements inherent in each development setting and, by using the same methodology to understand each process I uncover the formative elements unique to each process. The uniquely structured analysis contributes to existing scholarship by illustrating how new play development serves or does not serve the playwright, how the relationship between dramaturg and writer affect the process, and to what extent the realities of each development model in question do or do not serve the needs of each project. The thorough analysis afforded by the model tests the three tenets of play development identified by scholarship on development dramaturgy and illuminates the inner workings of the development initiatives which are particular to each case study.
Keywords: dramaturgy; dramaturgy; play development; Tarragon Theatre; Nightswimming Theatre